فعالية بعض الاختبارات العقلية المختارة للتطبيق لتشخيص حالات صعوبات تعلم الرياضيات - رمانة, عيسى; بن عيسى, خالد (جامعة الوادي- university eloued, 2017)
سعت الدراسة الحالية للكشف عن فعالية بعض الاختبارات العقلية المختارة للتطبيق، لتشخيص حالات صعوبات تعلم الرياضيات، وانطلاقا من التناول المعرفي الذي حدد أهم العمليات المعرفية المتحكمة في تعلم الرياضيات، الإدراك البصري، التذكر البصري، التمثيل الفضائي، والانتباه. تم تطبيق مجموعة من الاختبارات العقلية (WISC ،NEMI 2، الشكل المعقد ل REY، اختبار رسم الرجل، المصفوفات المتتابعة الملون، التنظيم البياني للإدراك، توجيه اليمين واليسار)، على عينة من التلاميذ ذوي النتائج الضعيفة في الرياضيات، وخلصت الدراسة إلى نتائج جد مهمة تمثلت في قدرة هذه المقاييس على تشخيص أهم الصعوبات التي يواجهها التلاميذ، ذات علاقة بالاضطراب الذي يمس إحدى العمليات العقلية السابقة الذكر، والتي ثمنت القيمة التشخيصية للاختبارات المختارة. The present study sought to reveal the effectiveness of mental tests selected for application, to diagnose cases of difficulties in learning mathematics, From the cognitive approach, which identified the most important processes controlling knowledge in learning mathematics, Visual perception, Visual remember, space representation and attention, Been applied to a range of mental tests:(NEMI 2 – WISC- complex figure for REY- Draw a man test- Successive color matrices- Organization chart for cognition- Steer left and right), a sample of students with weak results in mathematics. The study found very important results was the diagnosis main difficulties faced by students, related to the disorder, which affects one of the above mental processes, which also praised the value of diagnostic tests.
مقال
Keywords: الاختبارات العقلية ; صعوبات تعلم الرياضيات; mental tests; Difficulties in learning mathematics.